2018
DOI: 10.1615/jlongtermeffmedimplants.2017020737
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of All Smart Phone Applications Specifically Aimed for Use as a Scoliosis Screening Tool

Abstract: The scoliometer is an inclinometer commonly used in scoliosis screening. The device is used during an Adam's forward bend test, in which a patient bends forward at the hips to measure deformity of the rib cage and spinal column. If a sufficient angle of rotation is measured, then the appropriate referrals and x-rays can be made and taken. This ubiquitous screening tool allows for a quick and simple scoliosis screening and is a mainstay of scoliosis management. With the advent and rapid improvement of smart pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Most studies used a specific smartphone with a single application [12,14,16,17,20] where in our study both android and IOS smartphones with two different inclination applications were used with excellent accuracy and precision. This was also shown in a systematic review by Naziri et al [13] where different available smartphone applications can be used effectively.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Most studies used a specific smartphone with a single application [12,14,16,17,20] where in our study both android and IOS smartphones with two different inclination applications were used with excellent accuracy and precision. This was also shown in a systematic review by Naziri et al [13] where different available smartphone applications can be used effectively.…”
Section: Discussionmentioning
confidence: 57%
“…So far, several studies [12][13][14][15][16][17] showed that smartphones can be effectively used. Our mission is to set up a home screening program via patient empowerment; we want to examine its validity when used by parents compared to health-care physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Naziri et al [ 29 ] tried to cover this knowledge gap by testing the accuracy of four different smartphone applications (two on iOS and two on Android) using the sine bar as the gold standard. They used the Scoliogauge and ScoliTrack on an iPhone 5 and Scoliometer and Scoliosis Measurement on a Samsung Galaxy S3.…”
Section: Discussionmentioning
confidence: 99%
“…scoliometer was also included but not otherwise commented on, and it is unclear what it was. The authors [ 29 ] did not indicate whether they assessed both directions, and reported mean difference values of −0.14° (SD.31°) for the ScoliTrack, −0.12° (SD 0.12°) for the Scoliogauge, 0.82° (SD 1.52°) for the Android Scoliometer, and 2.26° (SD 1.28°) for the Android Scoliosis Measurement. The iOS applications using the specific iPhone device produced results similar to that of this study when compared to measurements to the left (mean difference 0.18° with SD 0.15°), but less similar when compared to the right (mean difference 0.03°, SD 0.03°).…”
Section: Discussionmentioning
confidence: 99%
“…However, research questions in those studies did not cover assessment methods based on mobile applications. Other reviews have also been performed but with a focus on anthropometric measures [16] or on applications available in application stores [17], which are not tested and validated experimentally with results presented in the research articles.…”
Section: Introductionmentioning
confidence: 99%